THE DEMOGRAPHIC SITUATION IN UZBEKISTAN IN LIGHT OF SOCIAL SECURITY - MAKSAKOVA, Ludmila (CENTRAL ASIA AND THE CAUCASUS, 2012)
Demographic development issues in today’s world are undeniably important. The rapid growth of the world’s population, shortage of resources, and increase in migration are creating numerous difficulties in affording a dignified standard and quality of life on the planet. The size of a country’s population, its distribution, and its gender-age composition frequently come forward as strategic factors in economic development and the formation of its future parameters.The demographic situation takes shape during population reproduction, the intensity of which determines the size and gender-age composition of the population, as well as the dynamics of its changes. It is characterized by several demographic indicators that have been prevailing in a particular territory over a specific period of time. The main ones are the birth rate, death rate, migration, marriages, and divorces. As the world becomes globalized, promoting a favorable demographic situation that maintains a balance among the interests of family, society, and the state is very important for the social stability and national security of any country.Demographic security is the most important component of social security. It reflects the level of the state’s protection from demographic threats, that is, from phenomena and trends that could have a negative effect on the country’s social stability and sustainable development. This concept is relatively new. According to several specialists, the demographic crisis in a whole number of countries, particularly industrially developed ones, which in some cases has escalated into a demographic catastrophe, has made it necessary to place demographic security in a separate category on an equal footing with economic, military, social, and other forms of security.This article examines the demographic situation in Uzbekistan from the viewpoint of global demographic development, as well as in the light of the possible risks and threats that might appear with respect to the republic’s social security.